Studi Pemasangan Low Pressure Economizer di Pembangkit Listrik Tenaga Uap (PLTU): Study on Installation of Low Pressure Economizer in Steam Power Plant (PLTU) - Shaumi, Annisa Fitri; Dani Rusirawan (Universitas Pendidikan Ganesha, 2024)
Steam Power Plants are widely used in various industries. To generate energy, coal is needed for the fuel, but coal supplies are running low, and coal can also cause side effects on the environment. To reduce coal consumption, energy efficiency are needed, one of improvement is to installation additional equipment, namely an economizer. The economizer functions is to reuse waste heat from the steam power generation process so that the heat produced is not wasted. There are two types of economizers, namely High Pressure Economizer (HPE) and Low Pressure Economizer (LPE). In this journal review, we will discuss the installation of LPE from various research perspectives so that we can find out the results after additional installation of this equipment. There is an analysis of the use of HPE, Organic Rankine Cycle (ORC), thermodynamic analysis, optimal design analysis, energy efficiency analysis, economic analysis, environmental analysis (emissions) and water savings in the Flue Gas Desulfurizer.